Molecular basis of UG-rich RNA recognition by the human splicing factor TDP-43 - Lukavsky, Peter J; Daujotyte, Dalia; Tollervey, James R; Ule, Jernej; Stuani, Cristiana; Buratti, Emanuele; Baralle, Francisco E; Damberger, Fred F; Allain, Frédéric H-T (Nature structural & molecular biology, 2013)
TDP-43 encodes an alternative-splicing regulator with tandem RNA-recognition motifs (RRMs). The protein regulates cystic fibrosis transmembrane regulator (CFTR) exon 9 splicing through binding to long UG-rich RNA sequences and is found in cytoplasmic inclusions of several neurodegenerative diseases. We solved the solution structure of the TDP-43 RRMs in complex with UG-rich RNA. Ten nucleotides are bound by both RRMs, and six are recognized sequence specifically. Among these, a central G interacts with both RRMs and stabilizes a new tandem RRM arrangement. Mutations that eliminate recognition of this key nucleotide or crucial inter-RRM interactions disrupt RNA binding and TDP-43-dependent splicing regulation. In contrast, point mutations that affect base-specific recognition in either RRM have weaker effects. Our findings reveal not only how TDP-43 recognizes UG repeats but also how RNA binding-dependent inter-RRM interactions are crucial for TDP-43 function.
Keywords: zastoupení bazí; sestřih RNA; RNA Splicing; protein CFTR; vazebná místa; Cystic Fibrosis Transmembrane Conductance Regulator; Protein Structure, Tertiary; terciární struktura proteinů; molekulární sekvence - údaje; Amino Acid Sequence; DNA vazebné proteiny; molekulární modely; Models, Molecular; Binding Sites; lidé; Humans; RNA-Binding Proteins; Base Composition; nukleární magnetická rezonance biomolekulární; sekvence aminokyselin; Molecular Sequence Data; DNA-Binding Proteins; proteiny vázající RNA; Nuclear Magnetic Resonance, Biomolecular